Effect of the antipsychotic agent amisulpride on glucose lowering and insulin secretion - Roix, J.; Decrescenzo, G.; Cheung, P.; Ciallella, J.; Sulpice, T.; Saha, S.; Halse, Rhiannon (2012)
Aims: To investigate the effects of the second generation antipsychotic (R/S)-amisulpride, and the chirally purified enantiomers, on glucose homeostasis in diet-induced obese (DIO) mice. Methods: Normal and DIO mice were treated with pharmacologically relevant doses of amisulpride prior to oral glucose tolerance tests (OGTTs). Blood glucose, insulin, glucagon-like peptide-1, prolactin and amisulpride drug levels were determined. Results: Racemic amisulpride significantly reduced glucose excursions during OGTT in both normal and DIO mice. This potent effect was preserved with the 'off-isomer', R-amisulpride (ED 50 1 mg/kg). Insulin secretion was significantly increased with R-amisulpride with only a minor increase in prolactin levels. Conclusions: Amisulpride has antidiabetic actions in DIO mice resulting from increased insulin secretion. This provides some explanation for why amisulpride, unlike other atypical antipsychotics, is not diabetogenic in man. Furthermore, the observation that R-amisulpride is also antidiabetic and has minimal impact on prolactin levels presents the opportunity for development of this isomer as an antidiabetic agent. © 2011 Blackwell Publishing Ltd.